Gaya Komunikasi Transformasional pada Gojek sebagai Aplikasi On-Demand di Indonesia - Novianti Sari Dewi; Ahmad Toni (MUKASI: Jurnal Ilmu Komunikasi, 2025)
Gojek is the largest on-demand service platform in Indonesia and a pioneer of the ecosystem model, offering various services including transportation, food delivery, logistics, and digital payments. Gojek requires leadership that is capable of maintaining good communication across all levels of the organization. Effective leadership communication is crucial at Gojek, given the dynamic and multi-service nature of its business, as well as the complexity of coordination across the various cities and countries where the company operates. This study aims to analyze the role of transformational leadership communication in supporting innovation and collaboration at Gojek. The method employed is a descriptive, qualitative case study approach to explore the application of transformational leadership in managing geographically dispersed and culturally diverse teams. Data collection was conducted through literature review and covert observation. The findings reveal that Gojek employs an adaptive, participatory, and innovative leadership communication style. This style effectively motivates employees, strengthens collaboration, enhances performance, and generates positive social impact within its ecosystem. These findings contribute to understanding how communication strategies in leadership support digital transformation and sustainable business development.